Adaptasi Pembelajaran Bahasa Indonesia Pada Masa Pandemi di Sekolah Dasar Penyelenggara Pendidikan Inklusif - Muhaimi Mughni Prayogo; Nur Indah Sholikhati (PLD UIN Sunan Kalijaga, 2021)
Mastering Indonesian language for all students is important despite the Covid-19 pandemic. Based on students' conditions and government provisions related to the pandemic, the teachers need a form of adaptation in the Indonesian language learning for students with disabilities in inclusive schools. This qualitative research finds adaptations of Indonesian language learning for students with special needs in twelve inclusive schools in five Yogyakarta's districts during the Covid-19 pandemic. Using a purposive sampling, 15 classroom teachers and special education staff were selected as key informants. Data was collected by interview, documentation, and literature study. Learning adaptation based on the conditions of the students' abilities emphasizes the modification and accommodation of learning strategies that include material, methods, media, and evaluation.[Pandemi Covid-19 tidak mengubah pentingnya kompetensi Bahasa Indonesia sebagai kemampuan akademik dasar bagi semua siswa. Berdasarkan keragaman kondisi siswa difabel dan ketentuan pemerintah terkait pandemi, guru perlu melakukan adaptasi pembelajaran Bahasa Indonesia di sekolah inklusif. Penelitian kualitatif ini menemukan berbagai bentuk adaptasi pembelajaran Bahasa Indonesia bagi siswa difabel khusus di sekolah inklusif di Daerah Istimewa Yogyakarta (DIY) pada masa pandemi Covid-19. Penelitian menunjukkan bahwa adaptasi pembelajaran mencakup materi, metode, media, dan evaluasi. Adaptasi pembelajaran dalam situasi pandemi Covid-19 ialah pelaksanaan pembelajaran dari rumah dengan penerapan strategi pembelajaran kontekstual yang menggunakan teknologi sebagai media interaksi dan konten materi.]